Commoning Cosmopolitanism: Solidarity Beyond Capital, Borders, and Sameness - Óscar García Agustín; Martin Bak Jørgensen (Social Inclusion)
Approaches to situated and located cosmopolitanism offer the opportunity to think of the formation of a universal community, which demands equality and social justice and is rooted in urban and local practices. This article delves into this perspective by connecting the literature on cosmopolitanism, the commons, and solidarity. Based on a sociospatial conception of solidarity, the notion of “commoning cosmopolitanism” is developed as a framework to understand how solidarity forges relationships where both commonalities and diversity can coexist. Three aspects are important to consider: (a) class struggle, as a response to exclusion and domination and the need to think relations beyond the logic of capital; (b) space, since the relationships are constituted spatially, connecting local and global scales and questioning the logic of borders; and (c) community, opposed to closed identities and “sameness,” and aiming to include previously excluded groups and establish a common ground whilst preserving multiplicity. Several examples are used to show how commoning cosmopolitanism allows us to consider the universal dimension of urban solidarity and the inclusion of migrants as part of the political community (the cosmopolitan “we”).